AI-Guided Synergistic Anticancer Potential of Peganum hamala and Black Garlic (Allium nigrum): A Systematic Review of Mechanistic Insights and Preclinical Evidence - Albukhari, Abdullah Faisal (Pharmacognosy Reviews)
Peganum harmala and black garlic (Allium nigrum) are traditional medicinal plants recognized for their unique anticancer effects. Recent studies indicate that their phytochemical components may work together synergistically to influence cancer pathways. This study aims to systematically analyze the anticancer mechanisms associated with P. harmala and black garlic, evaluate the predicted synergy through AI models, and identify areas where further research is needed. A systematic review was performed in accordance with PRISMA 2020 guidelines. Preclinical studies encompassing in vitro, in vivo, and in silico methodologies related to either plant were gathered from databases including PubMed, Scopus, Web of Science, and Google Scholar. A total of eighteen studies met the criteria for inclusion. Compounds found in P. harmala (such as harmine and harmaline) were observed to induce apoptosis and arrest cell cycle progression. Meanwhile, constituents of black garlic (including S-allyl cysteine and DADS) were noted for their role in modulating oxidative stress and survival signaling pathways. In silico analyses using tools like AutoDock and STITCH suggested a synergistic interaction by binding to common targets such as Bcl-2, caspase-9, and MAPK1. The combination of P. harmala and black garlic exhibits significant mechanistic complementarity along with AI-supported evidence of synergy. Further experimental validation is essential to transition this innovative phytotherapeutic strategy into clinical trials.
Keywords: Peganum harmala; Black Garlic; S-allyl Cysteine; Harmine; Cancer; Apoptosis; Molecular Docking; Artificial intelligence; Phytotherapy; Synergy; Network pharmacology; Colorectal cancer; Prostate cancer